2011
DOI: 10.1016/j.jfms.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of Remifentanil or Alfentanil in Propofol-Anesthetized Cats Undergoing Ovariohysterectomy

Abstract: Sixteen cats were used to compare the cardiovascular and anesthetic effects of remifentanil (REMI) or alfentanil (ALF) in propofol-anesthetized cats undergoing ovariohysterectomy. After premedication with acepromazine, anesthesia was induced and maintained with a constant rate infusion of propofol (0.3 mg/kg/min). REMI or ALF infusions were administered simultaneously with propofol. Heart rate (HR), systolic arterial pressure (SAP), pulse oximetry (SpO(2)), rectal temperature (RT), and response to surgical sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Its use in cats, as a total intravenous anaesthesia (TIVA), alone or associated with opioids, has been described by various investigators (Ilkiw and Pascoe 2003, Mendes and Selmi 2003, Padilha and others 2011, Boudreau and others 2012). In one study (Liehmann and others 2006), the authors reported propofol-based TIVA as being advantageous over isoflurane in injured cats by virtue of its greater haemodynamic stability (arterial blood pressure was better maintained).…”
Section: Introductionmentioning
confidence: 99%
“…Its use in cats, as a total intravenous anaesthesia (TIVA), alone or associated with opioids, has been described by various investigators (Ilkiw and Pascoe 2003, Mendes and Selmi 2003, Padilha and others 2011, Boudreau and others 2012). In one study (Liehmann and others 2006), the authors reported propofol-based TIVA as being advantageous over isoflurane in injured cats by virtue of its greater haemodynamic stability (arterial blood pressure was better maintained).…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged recovery time was to be expected as dogs were given a propofol-opioid infusion for approximately an hour. Prolonged propofol infusions cause significantly delayed anaesthetic recoveries in cats (Padilha et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Each drug could partially attenuate the undesirable effects of the other (Ilkiw et al 2003). The safety and stability of this combination have been documented (Vuyk et al 1996;Mendes and Selmi 2003;Auckburally et al 2008;Padilha et al 2011). However, prior work largely evaluated the effect of continuous infusions for procedural sedation and with variable ratios of propofol and alfentanil.…”
mentioning
confidence: 99%
“…The safety and stability of propofol combination have been documented (Auckburally et al, 2008;Padilha et al, 2011). Moreover, drug combinations typically reduce the dose of general anaesthesia or other anaesthetic which may be beneficial in certain situations (Smischney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%